Healthcare without borders: A cross-sectional study of immigrant and nonimmigrant children admitted to a large public sector hospital in the Gauteng Province of South Africa - Janse van Rensburg, Gerhard H. (PLoS Med, 2021)
BACKGROUND: Human migration is a worldwide phenomenon that receives considerable attention from the media and healthcare authorities alike. A significant proportion of children seen at public sector health facilities in South Africa (SA) are immigrants, and gaps have previously been noted in their healthcare provision. The objective of the study was to describe the characteristics and differences between the immigrant and SA children admitted to Kalafong Provincial Tertiary Hospital (KPTH), a large public sector hospital in the urban Gauteng Province of SA. METHODS AND FINDINGS: A cross-sectional study was conducted over a 4-month period during 2016 to 2017. Information was obtained through a structured questionnaire and health record review. The enrolled study participants included 508 children divided into 2 groups, namely 271 general paediatric patients and 237 neonates. Twenty-five percent of children in the neonatal group and 22.5% in the general paediatric group were immigrants. The parents/caregivers of the immigrant group had a lower educational level (p < 0.0001 neonatal and paediatric), lower income (neonatal p < 0.001; paediatric p = 0.024), difficulty communicating in English (p < 0.001 neonatal and paediatric), and were more likely residing in informal settlements (neonatal p = 0.001; paediatric p = 0.007) compared to the SA group. In the neonatal group, there was no difference in the number of antenatal care (ANC) visits, type of delivery, gestational age, and birth weight. In the general paediatric group, there was no difference in immunisation and vitamin A supplementation coverage, but when comparing growth, the immigrant group had more malnutrition compared to the SA group (p = 0.029 for wasting). There was no difference in the prevalence of maternal human immunodeficiency virus (HIV) infection, with equally good prevention of mother-to-child transmission (PMTCT) coverage. There was also no difference in reported difficulties by immigrants in terms of access to healthcare (neonatal p = 0.379; paediatric p = 0.246), although a large proportion (10%) of the neonates of immigrant mothers were born outside a medical facility. CONCLUSIONS: Although there were health-related differences between immigrant and SA children accessing in-hospital care, these were fewer than expected. Differences were found in parental educational level and socioeconomic factors, but these did not significantly affect ANC attendance, delivery outcomes, immunisation coverage, HIV prevalence, or PMTCT coverage. The immigrant population should be viewed as a high-risk group, with potential problems including suboptimal child growth. Health workers should advocate for all children in the community they are serving and promote tolerance, respect, and equal healthcare access.